Bilateral Comminuted Mandibular Fracture Caused by Gunshot Wound: Case Report Using Prototyping to Assist Surgical Planning - Tavares Palmeira, Julia; Lima, Diego Learth; Gondim, Ricardo Franklin; Menezes Junior, José Maria Sampaio; Pinto, Clarice Maia Soares de Alcântara (Brazilian Journal of Case Reports, 2024)
The mandible is one of the facial bones most frequently affected in maxillofacial trauma, and firearm projectiles have shown an increase in incidence among the etiological factors of these fractures. Choosing the optimal timing for surgical intervention is challenging, given the degree of bone comminution and the potential complications that these fractures can present. This paper reports the case of a 36-year-old male patient, with poorly controlled diabetes, admitted to an intensive care unit in a municipal tertiary hospital of the public network in Fortaleza, Ceará, Brazil, as a victim of multiple gunshot wounds. Facial computed tomography showed a comminuted bilateral mandibular body fracture with the presence of metallic structures compatible with projectile fragments. The treatment plan was staged in two surgical phases, beginning with surgical debridement and maxillomandibular fixation. Next, pre-molded 2.4 mm reconstruction plates were installed on a 3D-printed prototype. The patient progressed without complications or clinical complaints and remained under clinical and radiographic follow-up during the postoperative period. Thus, it can be concluded that the use of three-dimensional prototypes for pre-molding reconstruction plates is an excellent tool for achieving proper plate adaptability to the bone profile and for reducing intraoperative time.